2015
DOI: 10.1007/s00464-015-4646-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reactive oxygen species on the physical properties of polypropylene surgical mesh at various concentrations: a model for inflammatory reaction as a cause for mesh embrittlement and failure

Abstract: The results demonstrated that a 6-month exposure to a physiologic range of ROS (1 mM) decreased tensile strength of PP mesh by 31 %. 1 mM and 0.1 M samples behaved similarly demonstrating properties of a quasi-crystalline nature. 1 M samples displayed qualities of extreme embrittlement. Scanning electron microscopy (SEM) observed fiber changes. 1 M meshes had features of brittle materials. Knowledge of changes in physical properties of PP meshes is useful for considerations for the development of a more biocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…23 Reactive oxygen species create oxidative changes in the polypropylene, resulting in cracks, surface roughness and peeling, loss of mass, decreased compliance, and embrittlement over time, potentially leading to material failure. 24,25 Among the most feared complications in VHR is mesh infection, and mesh removal is often indicated. We found that large-pore PP, both MWPP and LWPP, are remarkably able to resist chronic infection, and no PP mesh was removed in our study because of infection, although two were taken out at the time of reexploration for missed enterotomy, and were not replaced at that time because of the clinical condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…23 Reactive oxygen species create oxidative changes in the polypropylene, resulting in cracks, surface roughness and peeling, loss of mass, decreased compliance, and embrittlement over time, potentially leading to material failure. 24,25 Among the most feared complications in VHR is mesh infection, and mesh removal is often indicated. We found that large-pore PP, both MWPP and LWPP, are remarkably able to resist chronic infection, and no PP mesh was removed in our study because of infection, although two were taken out at the time of reexploration for missed enterotomy, and were not replaced at that time because of the clinical condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…High mechanical properties (i.e., elastic modulus of 2-4 GPa and strength of 50-100MPa) and enhanced tissue integration of SRT further helped to result in significantly less cranio-caudal shrinkage compared to uncoated PP mesh. Inflammation is known to increase tissue fibrosis across a wide spectrum of implants (37) fostering material embrittlement and fragmentation (38). These unique properties of SRT allow it to function better than other synthetic and biologic meshes, which can experience significant shrinkage (39) as demonstrated in both animal studies and clinically (15).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the meshes used nowadays are knitted from monofilament polypropylene. Polypropylene is affordable, chemically inert, and able to withstand sterilization while retaining flexibility [5]. Porosity of the mesh suggests the enhanced tissue integration and the reduced foreign body reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chief among post-hernioplasty complications is chronic pain, which has been reported in nearly 30% of patients [7]. While the exact cause of the chronic pain has not been established yet, lack of material inertness in vivo and oxidative environment induced by inflammatory cells in the incision area appear to be the key factors in poor mesh performance [2,5,8]. White blood cells are recruited at the interface between tissue and mesh fibers within minutes to hours after the implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation